2014
DOI: 10.1021/om5006676
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tungsten Imido Alkylidene Complexes that Contain an Electron-Withdrawing Imido Ligand

Abstract: Tungsten NArR alkylidene complexes have been prepared that contain the electron-withdrawing ArR groups 2,4,6-X3C6H2 (ArX3, X = Cl, Br), 2,6-Cl2-4-CF3C6H2 (ArCl2CF3), and 3,5-(CF3)2C6H3 (Ar(CF3)2). Reported complexes include W(NArR)2Cl2(dme) (dme = 1,2-dimethoxyethane), W(NArR)2(CH2CMe3)2, W(NArR)(CHCMe3)(OTf)2(dme), and W(NArR)(CHCMe3)(ODBMP)2 (DBMP = 4-Me-2,6-(CHPh2)C6H2). The W(NArR)(CHCMe3)(ODBMP)2 complexes were explored as initiators for the polymerization of 2,3-dicarbomethoxynorbornadiene (DCMNBD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For example, a diionic tetraphenylporphyrin ruthenium 3,5-bisCF 3 bisimido complex reported by Gallo and co-workers features Ru–N–C angles of 139.8(3)° and 143.7(4)° which demonstrates that the lone pair of the N imido is not datively bound to the Ru center and is available for reactivity . Additionally, Schelter and co-workers reported a series of cerium imido complexes with 3,5-bisCF 3 substituents where the lone pair of the N imido is datively bound to alkali metal countercations, rather than the cerium center, resulting in acute Ce–N imido –C angles ranging from 125.4(2) to 157.3(4)°. , On the other hand, there are examples of metal imidos with 3,5-bisCF 3 substituents where the lone pair on the N imido is datively bound to the metal center resulting in a more linear angle, 166.8(2)–179.2(7)°. These U–N imido –C angles suggest that there is a dative interaction between the uranium center and the lone pair on the N imido atom for 3-pF , 3-bisF , 3-Mes , and 3-Mes* . Interestingly, the acute U–N imido –C angle in 3-bisCF 3 suggests a weakened dative interaction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, a diionic tetraphenylporphyrin ruthenium 3,5-bisCF 3 bisimido complex reported by Gallo and co-workers features Ru–N–C angles of 139.8(3)° and 143.7(4)° which demonstrates that the lone pair of the N imido is not datively bound to the Ru center and is available for reactivity . Additionally, Schelter and co-workers reported a series of cerium imido complexes with 3,5-bisCF 3 substituents where the lone pair of the N imido is datively bound to alkali metal countercations, rather than the cerium center, resulting in acute Ce–N imido –C angles ranging from 125.4(2) to 157.3(4)°. , On the other hand, there are examples of metal imidos with 3,5-bisCF 3 substituents where the lone pair on the N imido is datively bound to the metal center resulting in a more linear angle, 166.8(2)–179.2(7)°. These U–N imido –C angles suggest that there is a dative interaction between the uranium center and the lone pair on the N imido atom for 3-pF , 3-bisF , 3-Mes , and 3-Mes* . Interestingly, the acute U–N imido –C angle in 3-bisCF 3 suggests a weakened dative interaction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…p -Toluenesulfonyl hydrazide ( p -Tos-NHNH 2 ) was purchased from Sigma-Aldrich and was used without further purification. Mo­(NAr)­(CHCMe 2 Ph)­(O- t- Bu) 2 ( 1 ; NAr = N-2,6- i- Pr 2 C 6 H 3 ), W­(N- t- Bu)­(CHCMe 3 )­(pyr)­(OHMT) ( 2 , OHMT = O-2,6-(2,4,6-Me 3 C 6 H 2 ) 2 C 6 H 3 ), W­(NAr)­(CHCMe 2 Ph)­(pyr)­(OHMT) ( 3 ), W­(N-2,6-Me 2 C 6 H 3 )­(C 3 H 6 )­(pyr)­(OHIPT) ( 4 , OHIPT = O-2,6-(2,4,6- i- Pr 3 C 6 H 2 ) 2 C 6 H 3 ), W­(O)­(CHCMe 2 Ph)­(Me 2 Pyr)­(OHMT)­(PMePh 2 ) ( 7 ), W­(O)­(CHCMe 2 Ph)­(Me 2 Pyr)­(OHMT)­(MeCN) ( 8 ), W­(O)­(CHCMe 2 Ph)­(Me 2 Pyr)­(ODFT)­(PMePh 2 ) ( 9 , ODFT = O-2,6-(C 6 F 5 ) 2 C 6 H 3 ), W­(O)­(CHCMe 2 Ph)­(Me 2 Pyr)­(OTPP)­(PMePh 2 ) ( 10 , OTPP = O-2,3,5,6-Ph 4 C 6 H), W­(O)­(CHCMe 2 Ph)­(Me 2 Pyr)­(ODPP)­(PMePh 2 ) ( 11 , ODPP = O-2,6-Ph 2 C 6 H 3 ), Mo­(N- t- Bu)­(CHCMe 3 )­(pyr)­(OHMT) ( 12 ), Mo­(NAd)­(CHCMe 3 )­(pyr)­(OHMT) ( 13 ; Ad = 1-adamantyl), Mo­(NAr)­(CHCMe 2 Ph)­(Me 2 pyr)­(ODPP) ( 14 ), Mo­(NAr)­(CHCMe 2 Ph)­(pyr)­(OHMT) ( 15 ), Mo­(N-2,6-Me 2 C 6 H 3 )­(CHCMe 3 )­(pyr)­(OHIPT) ( 16 ), Mo­(N-2,6-Me 2 C 6 H 3 )­(CHCMe 2 Ph)­( rac -biphen) ( 17 , biphen =3,3′-( t- Bu) 2 -5,5′-6,6′-(CH 3 ) 4 -1,1′-biphenyl-2,2′-diolate), Mo­(NAr)­(CHCMe 2 Ph)­( rac -biphen- t- Bu) ( 18 , biphen- t- Bu = 3,3′-( t- Bu) 2 -5,5′-( t- Bu) 2 -6,6′-(CH 3 ) 2 -1,1′-biphenyl-2,2′-diolate), Mo­(NAd)­(CHCMe 2 Ph)­( rac -biphen- t- Bu) ( 19 ), Mo­(N-2,6-Me 2 C 6 H 3 )­(CHCMe 2 Ph)­(THF)­( rac -biphenCF 3 ) ( 20 , biphenCF 3 = 3,3′-( t- Bu) 2 -5,5′-(CF 3 ) 2 -6,6′-(CH 3 ) 2 -1,1′-biphenyl-2,2′-diolate), Mo­(NAd)­(CHCMe 2 Ph)­(THF)­( rac -biphenCF 3 ) ( 21 ), W­(N-2,6-Me 2 C 6 H 3 )­(CHCMe 2 Ph)­( rac -biphen) ( 22 ), W­(O)­(CHCMe 2 Ph)­(OHMT) 2 ( 23 ), W­(O)­(CHCMe 2 Ph)­(OTPP) 2 (PMePh 2 ) ( 24 ), W­(NC 6 F 5 )­(CHCMe 3 )­(ODFT) 2 ( 25 ), W­(N-2,4,6-Cl 3 C 6 H 2 )­(CHCMe 3 )­(O-2,6-(CHPh 2 ) 2 -3-MeC 6 H 2 ) 2 ( 26a ), W­(N-2,4,6-Br 3 C 6 H 2 )­(CHCMe 3 )­(O-2,6-(CHPh 2 ) 2 -3-MeC 6 H 2 ) 2 ( 26b ), W­(N-2,4,6-Cl 3 C 6 H 2 )­(CHCMe 3 )­(OTf) 2 (dme), and W­(O)­(CHCMe 2 Ph)­(Me 2 Pyr) 2 (PPh 2 Me) were prepared according to published procedures.…”
Section: Methodsmentioning
confidence: 99%
“…p-Toluenesulfonyl hydrazide (p-Tos-NHNH 2 ) was purchased from Sigma-Aldrich and was used without further purification. Mo(NAr)(CHCMe 27 and W(O)(CHCMe 2 Ph)(Me 2 Pyr) 2 (PPh 2 Me) 28 were prepared according to published procedures.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Hoveyda and co-workers have shown that modification of the imido fragment to be more electron deficient and less sterically encumbered, in complexes of the type W(NAr)(CHCMe3)(ODBMP)2 (DBMP = 2,6-CHPh2-4-Me-C6H2), led to much higher rates of polymerisation of 2,3-dicarbomethoxynorbornadiene. 5 In 1975, Menapace et al reported that the selectivity of a metathesis catalyst comprised of WCl6, PhNH2 and Et3Al2Cl3 could be modified in favour of alkene dimerisation by increasing the amount of aluminium cocatalyst in the system. 6 Furthermore, addition of triethylamine into the system with EtAlCl2 as the cocatalyst resulted in selectivities >99% for the dimerisation of 1-hexene.…”
Section: Introductionmentioning
confidence: 99%